VPN SOLUTIONS: BALANCING PRODUCTIVITY AND SECURITY FOR BUSINESS - Thomas, Reji Kurien (Global journal of Business and Integral Security, 2023)
The COVID-19 pandemic resulted an increase in teleworking to ensure that businesses and employees could continue to function. Teleworking has been acknowledged to have both advantages and challenges. Nevertheless, its success in supporting continuity of business operations has resulted in organisations continuing to support it, in full-time or hybrid modes, even after the pandemic. Relatedly, different technologies have been used to support telework. In this thesis, the impact of using virtual private networks (VPNs) to support productivity and security while organisations continue to allow their employees to telework is studied. The outcomes of this study can help organisations finetune models of work which include teleworking. Moreover, the insights may help organisations redesign work and schedules for different levels of employees.